2010
DOI: 10.1002/cphc.201000213
|View full text |Cite
|
Sign up to set email alerts
|

Probing Redox Reactions of Immobilized Cytochrome c Using Evanescent Wave Cavity Ring‐Down Spectroscopy in a Thin‐Layer Electrochemical Cell

Abstract: We report the use of evanescent wave cavity ring-down spectroscopy (EW-CRDS) to monitor the reduction by ethylenediaminetetraacetic acid iron(II) complex, [FeEDTA](2-), of an adsorbed layer of oxidized cytochrome c immobilized on fused silica. The adsorption of cytochrome c at the silica-water interface was also probed using EW-CRDS and found to be in qualitative agreement with previous studies. The reduction of the adsorbed cytochrome c was achieved by using a strategically positioned electrode to electrogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…38 In a subsequent work, it was used to change the solution pH in a controlled manner via the potential-pulsed chronoamperometric oxidation of water. 39 In another study, 40 it was applied to investigate the adsorption process of Cyt-C protein at a silica−water interface. In this last report, a chronoamperometry technique was applied to provide soluble redox mediators, which after diffusion, could chemically control the redox state of an adsorbed layer of Cyt-C species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…38 In a subsequent work, it was used to change the solution pH in a controlled manner via the potential-pulsed chronoamperometric oxidation of water. 39 In another study, 40 it was applied to investigate the adsorption process of Cyt-C protein at a silica−water interface. In this last report, a chronoamperometry technique was applied to provide soluble redox mediators, which after diffusion, could chemically control the redox state of an adsorbed layer of Cyt-C species.…”
mentioning
confidence: 99%
“…In another embodiment, a liquid/liquid interface was studied by the EW-CRDS technique with electrochemical potential control located in the bulk phase of one of the liquids . However, in all of these studies, the surface under optical interrogation by the EW-CRDS platform was not electrically active, so the redox process probed by the EW-CRDS optical signal was always limited by the mass diffusion of the redox agents, which certainly imposes limitations for many electrochemical studies, as for instance in investigations of time rates of charge transfer in redox events.…”
mentioning
confidence: 99%
“…29 An interesting recent application of evanescent wave cavity ring-down spectroscopy (EW-CRDS) to monitor the reduction of horse heart cytochrome c adsorbed at the silicawater interface in a thin-layer electrochemical cell has been demonstrated by Unwin and co-workers. 78 Although in this case the electron transfer was mediated by [Fe(EDTA)] 2À , and hence was diffusion limited, EW-CRDS is capable of following interfacial dynamics on sub-millisecond timescales 79 and is compatible with a variety of different interfaces. 80 Coupled with a suitable electrochemical cell that allows un-mediated direct electron transfer, therefore, EW-CRDS could present a useful addition to the suite of spectroelectrochemical methods employed to study the dynamics of electron transfer processes in redox proteins.…”
Section: Alternative Spectroelectrochemical Methodsmentioning
confidence: 93%
“…65 Our group recently used a thin layer electrochemical cell (similar to that described in Sections 2.2 and 2.3) to study the redox reaction between an adsorbed layer of cytochrome c immobilised on fused silica and the ethylenediaminetetraacetic acid iron(II) complex (FeEDTA 2À ). 66 This latter work showed that it is possible to directly monitor electron transfer between surface immobilised proteins and molecules using EW-CRDS, and obtain quantitative information on the kinetics.…”
Section: Biologically-relevant Interfacesmentioning
confidence: 98%